Evaluasi Kepuasan Pengguna Aplikasi Mobile MASTRIS UNJA Menggunakan System Usability Scale (SUS) - Fadillah, Muhammad Reno; Aryani, Reni; Muhammad Razi A. (Prodi Sistem Informasi FST Universitas Jambi, 2026)
Universitas Jambi (UNJA) launched MASTRIS UNJA, a mobile application that integrates SIAKAD, ELISTA, geolocation-based attendance, and electronic mail services. Following the 2.0.2 update released on 6 May 2026, an evaluation was required to determine whether the update improved user satisfaction, particularly for the SIAKAD and ELISTA features. This study measured usability using the System Usability Scale (SUS) with a sample of 97-100 active students of the Faculty of Science and Technology, determined using the Slovin formula. Data were collected through online and offline questionnaires and analyzed with Microsoft Excel following standard SUS scoring rules. The results show an average SUS score of 75.82, placing the application in Grade B, the “Good” adjective category, the “Acceptable” range, and the “Passive” Net Promoter Score category, with a percentile rank of approximately 74%. Per-indicator analysis shows the highest score on user confidence (item 9, mean 3.32) and the lowest on the need to become familiar with the system before use (item 10, mean 2.74). These findings indicate that the MASTRIS UNJA update has improved usability and is well accepted by users, although the learnability aspect still requires improvement.